Contributions to the knowledge of Macroheterocera (Lepidoptera) Fauna of Mutki District (Bitlis Province, East Turkey) - Kesran Akın; Erdem Seven (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This paper, contributesto the Macro-Heterocera fauna of Mutki district of Bitlis Province (EastTurkey) as a list. All given 192 species are recorded for the first time frommoth fauna of Mutki and likewise 85 species are recorded for thefirst time from moth fauna of Bitlis. Additionally, adult and genitalia of male Eupithecia gemellata Herrich-Schäffer, 1861and Chondrostega palaestranumStaudinger, 1892 are illustrated.